#TITLE_ALTERNATIVE# - USMAN HAKIM (NIM 224 04 003); Pembimbing : Sonny Winardhi, Ph.D., ARIF
Telisa Sandstone is the lower part of Telisa formation which consists of very fine to fine grained sandstones with minor shales, deposited in a shallow marine shoreface setting during both sea level lowstand and transgression in basin rim. The acoustic impedance contrast between the sandstones and the overlying and underlying Telisa shales is very small due to highly argillaceous content of the sandstone. This causes the sandstone reservoir prediction becomes very difficult. Study of Telisa sandstone reservoir characterization is performed to estimate reservoir distribution and its potential fluid content. The study is done by utilizing analysis of elastic parameter Lambda-Mu-Rho of wells from Kaji-Semoga, Kerang, Langkap and Rimbabat area and seismic 2D data of 46 seismic lines with various quality and vintages using inversion technique of Extended Elastic Impedance (EEI) method. Mu is the elastic parameter representing rock rigidity which can be used to help distinguishing lithology types. Meanwhile, Lambda represents rock incompressibility that can be utilized to help determine potential fluid content of reservoir. Results of analysis from wells and interpretation of elastic parameter map shows that Mu-Rho is a sensitive parameter to help distinguishing lithology type. Meanwhile, Lambda-per-Mu anomaly is used to help determine potential fluid content of the reservoir.